'For the cases we've had… I don't think anybody has had enormous confidence' – Exploring 'Uncertainty' in adolescent bariatric teams: an interpretative phenomenological analysis. Issue 1 (9th December 2013) - Doyle, J.; Colville, S.; Brown, P.; Christie, D.
Summary What is already known about this subject? Bariatric surgery is more effective for weight loss in severe obesity than lifestyle interventions. The number of bariatric surgery procedures carried out in England in adults has almost doubled between 2008 and 2011. Bariatric surgery is increasingly being offered to adolescents with severe obesity. What this study adds A predominant theme of 'uncertainty' around adolescent bariatric surgery emerged from the interviews. In the absence of empirical data, professionals bracket away this uncertainty by a variety of means, including the acceptance of surgery as inevitable. This study has implications for the effective counselling of adolescents and their families around bariatric surgery. Evidence suggests that bariatric surgery is increasingly being offered to adolescents with severe obesity despite the lack of long‐term outcome data or research to guide patient selection. This is a qualitative study in which nine clinicians were interviewed to investigate the process of decision‐making around adolescent bariatric surgery. The interviews revealed a pervasive 'uncertainty', with sources of uncertainty relating to (i) the lack of research in this area, (ii) the perception of bariatric surgery as a treatment option unlike others, (iii) the view that adolescence is a complex developmental period and (iv) the perception that bariatric in adolescents is controversial to the public. Professionals manage this uncertainty in a variety of ways, which are described. It is argued here that shedding light on this process of professional decision‐making has implications for policy and practice and for the counselling of patients considering these sorts of treatments.